INVESTIGATING THE RELATIONSHIP BETWEEN INSTITUTIONAL OWNERSHIP WITH FINANCIAL POLICIES AND PERFORMANCE OF LISTED COMPANIES IN TEHRAN STOCK EXCHANGE (Singaporean Journal of Business Economics and Management, 2015)
According to agency theory, "institutional owners" may reduce conflicts of agency through the monitoring of management measures and improve company performance. Institutional owners given ownership of significant proportion of company's shares have considerable influence in the investee companies and can affect their policies and procedures. They have motivates and also the expertise and resources needed to monitor the company. Hence, objective of this study is investigating the relationship between institutional ownership with financial policies and performance of listed companies in Tehran Stock Exchange. Thus it have been selected a total of 90 companies for the period 2006 to 2010. Pearson correlation and multiple regression analyzes were used in order to achieve the research objectives. The results show that institutional ownership has positive and significant relationship with dividend policy and have negative and significant relationship with financial leverage. There is negative relationship dividend policy and financial leverage. Also Results showed that there is positive and significant relationship between institutional ownership and performance using two criteria ROE and Tobin's Q. there isn't significant relationship between institutional ownership and ROA.